Technoeconomic analysis of pistachio waste utilization in combined heat and power systems in Iran - Mousa Meratizaman; Mojtaba Nateqi; Mohammad Taha Karami; Soheil Kananian (Discover Energy)
Abstract Seasonal energy shortages in Iran, caused by imbalances in electricity and natural gas production, call for innovative renewable energy solutions. This study evaluates the technical and economic viability of using pistachio waste for combined heat and power systems, a novel application in the region. Four scenarios are modeled using Cycle Tempo software: incineration with a steam cycle, and gasification with a biogas engine, solid oxide fuel cell, and gas turbine. Scenario 2, involving gasification with a biogas engine, emerges as the most economical, achieving a levelized cost of electricity of 3.6 US cents per kilowatt-hour and a prime cost of 2.53 US cents per kilowatt-hour, with a return period of 1.97 years. Scenario 3, using gasification with solid oxide fuel cells, offers the highest electrical efficiency of 41% but requires a longer return period. Environmental benefits include reducing methane emissions and natural gas consumption through heat recovery for greenhouse heating. The findings demonstrate pistachio waste’s potential as a sustainable feedstock for combined heat and power systems, contributing to energy diversification and environmental sustainability in Iran. Future research should explore scaling system capacity, integrating hybrid renewable systems, and advancing solid oxide fuel cell technology to enhance feasibility and adoption.